Strategic Leadership as the Primary Force of Islamic Boarding School for Sustainability - Binti; Qomar, Mujamil; Eko Sujianto, Agus (International journal of technology and education research, 2023)
With a predominantly Muslim population, Indonesia is developing a type of educational institution called Islamic boarding school (IBS). Along with the increasing needs of the community for the existence of these institutions, IBS leaders face the challenge of surviving in conditions of hypercompetition. IBS leaders are encouraged to be able to think strategically to be able to maintain develop the institution forward. This research was conducted to explore the strategic leadership activities of leader from an IBS, to make institution survive and develop rapidly in just 10 years. Through a qualitative approach, the results of the study found four strategic steps that the leader took in an effort: (1) create and communicate a vision; (2) core competencies building; (3) culture-structure management effectively; (4) Community bonding.